Intraoperative pharmacologic opioid minimisation strategies and patient-centred outcomes after surgery: a scoping review protocol. Issue 3 (1st March 2023) - Verret, Michael; Lam, Nhat Hung; Fergusson, Dean A; G Nicholls, Stuart; Turgeon, Alexis F; McIsaac, Daniel I; Gilron, Ian; Hamtiaux, Myriam; Srichandramohan, Sriyathavan; Al-Mazidi, Abdulaziz; A Fergusson, Nicholas; Hutton, Brian; et al.
Abstract : Introduction: For close to a century opioid administration has been a standard of care to complement anaesthesia during surgery. Considering the worldwide opioid epidemic, this practice is now being challenged and there is a growing use of systemic pharmacological opioid minimising strategies. Our aim is to conduct a scoping review that will examine clinical trials that have evaluated the impact of intraoperative opioid minimisation strategies on patient-centred outcomes and identify promising strategies. Methods and analysis: Our scoping review will follow the framework developed by Arksey and O'Malley. We will search MEDLINE, Embase, CENTRAL, Web of Science and CINAHL from their inception approximately in March 2023. We will include randomised controlled trials, assessing the impact of systemic intraoperative pharmacologic opioid minimisation strategies on patient-centred outcomes. We define an opioid minimisation strategy as any non-opioid drug with antinociceptive properties administered during the intraoperative period. Patient-centred outcomes will be defined and classified based on the consensus definitions established by the Standardised Endpoints in Perioperative Medicine initiative (StEP-COMPAC group) and informed by knowledge users and patient partners. We will use a coproduction approach involving interested parties. Our multidisciplinary team includes knowledge users, patient partners, methodologists and knowledge user organisations. Knowledge users will provide input on methods, outcomes, clinical significance of findings, implementation and feasibility. Patient partners will participate in assessing the relevance of our design, methods and outcomes and help to facilitate evidence translation. We will provide a thorough description of available clinical trials, compare their reported patient-centred outcome measures with established recommendations and identify promising strategies. Ethics and dissemination: Ethics approval is not required for the review. Our scoping review will inform future research including clinical trials and systematic reviews through identification of important intraoperative interventions. Results will be disseminated through a peer-reviewed publication, presentation at conferences and through our network of knowledge user collaborators. Registration: Open Science Foundation (currently embargoed)